Psychoeducational To Strengthen Social Interaction, Academic Integrity,And Multicultural Character Among Adolescents At MTS As-Salam Palembang - Itryah; Nadya Marsyah (Jurnal Pengabdian Masyarakat, 2026)
Purpose: The purpose of community service is to provide educational psychology to strengthen social interaction, academic integrity, and multicultural character among children at Mts As-Salam Palembang. Method: The community service activity employed a descriptive qualitative approach to describe the implementation process and outcomes based on field conditions. Data were collected through observation, documentation, activity sheets, and participants’ reflection sheets. Data analysis was conducted using data reduction techniques and presented in a narrative form. Practical Applications: The results of this study indicate that psychoeducation programs are effective and applicable for implementation in school settings, particularly in guidance and counseling services. Approaches based on group discussions, role-playing, value dilemmas, and self-reflection have been proven to improve students' social interaction, academic integrity, and tolerance in a sustainable manner. Conclusion: It can be concluded that the psychoeducational program was implemented successfully and achieved its intended objectives. The two-week program, consisting of four sessions, had a positive impact on improving participants’ social interaction, academic integrity, and tolerance. Students demonstrated more adaptive communication skills, a better understanding of academic honesty and responsibility, and more open and respectful attitudes toward differences.